2016
DOI: 10.1038/srep35243
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of ZnO and TiO2 to Escherichia coli cells

Abstract: We performed a comprehensive investigation of the toxicity of ZnO and TiO2 nanoparticles using Escherichia coli as a model organism. Both materials are wide band gap n-type semiconductors and they can interact with lipopolysaccharide molecules present in the outer membrane of E. coli, as well as produce reactive oxygen species (ROS) under UV illumination. Despite the similarities in their properties, the response of the bacteria to the two nanomaterials was fundamentally different. When the ROS generation is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(84 citation statements)
references
References 63 publications
(219 reference statements)
2
80
2
Order By: Relevance
“…The first involves the generation of free radicals, and this is considered the most common mechanism of nanoparticle‐induced cell toxicity. [ 54 ] Generally, reactive oxygen‐rich species, including hydroxyl ions, superoxide ions and hydrogen peroxide, are generated under UV illumination. Moreover, the annealing of ZnO nanoparticles under oxygen generates a large number of holes on the surface and consequently increases the surface area of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The first involves the generation of free radicals, and this is considered the most common mechanism of nanoparticle‐induced cell toxicity. [ 54 ] Generally, reactive oxygen‐rich species, including hydroxyl ions, superoxide ions and hydrogen peroxide, are generated under UV illumination. Moreover, the annealing of ZnO nanoparticles under oxygen generates a large number of holes on the surface and consequently increases the surface area of the material.…”
Section: Resultsmentioning
confidence: 99%
“…These types of ROS synergistically act by attacking polyunsaturated phospholipids leading to increased permeability of cell membrane and leaking out vital cell components which finally cause bacterial death [35]. Leung and his coworker [27] investigated the antibacterial activity of TiO 2 NPs on E. coli by scanning electron microscopy (SEM). Their results showed that TiO 2 NPs attached to bacteria followed by causing holes in their cell membrane and collapsing due to leakage of content.…”
Section: Discussionmentioning
confidence: 99%
“…FTN binding to the bacterial surface caused severe damage on cell membrane most probably because of ROS production. ROS disturbs membrane integrity by peroxidation of phospholipids leading to leakage of minerals, proteins and genetic materials ending with cell death [27].…”
Section: Characterizationmentioning
confidence: 99%
“…Overall, the considerable reduction in bacterial viability due to 10% ZnO addition is recorded. Many biochemical experiments show that reactive oxygen species (ROS) and oxidative stresses generated by ZnO kills the bacteria by rupturing the bacterial membrane . In addition, ZnO generates the hydroxyl radicals like H 2 O 2 and singlet oxygen, which cause the oxidation of membrane lipids of cell wall of bacteria …”
Section: Discussionmentioning
confidence: 99%